2021
DOI: 10.14716/ijtech.v12i2.4578
|View full text |Cite
|
Sign up to set email alerts
|

Micro-structured Materials for the Removal of Heavy Metals using a Natural Polymer Composite

Abstract: In this study, a precipitation method was employed to prepare a synthetic hydroxyapatite (HAP)/chitosan (CHN) composite by the modification of synthetic HAP with CHN. The HAP/CHN composite was characterized by Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy equipped with energy-dispersive X-ray spectroscopy (SEM-EDX). Furthermore, the HAP/CHN composite in a 1:1 ratio (wt.%) was investigated as an adsorbent for the removal of heavy metals ions (such as Cr 6+ , Cd 2+ and Zn 2+ ) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The Sm addition to the alloy changes the microstructure of the ZRE1 base alloy. Similarly, research by (Sheggaf et al, 2017) and (Kusrini et al, 2021) showed that ZRE1 base alloys microstructure changes with the addition of Pr. The addition of Sm shows a significant effect on ZRE1 grain size in Figure 5, where the addition of 0.5 wt.% Sm reduces the grain size significantly by about 13% due to an increase in the coherency time of the alloy (Ahmad et al, 2017b).…”
Section: Figure 3 Xrd Pattern Of Zre1-xsm Alloysmentioning
confidence: 79%
“…The Sm addition to the alloy changes the microstructure of the ZRE1 base alloy. Similarly, research by (Sheggaf et al, 2017) and (Kusrini et al, 2021) showed that ZRE1 base alloys microstructure changes with the addition of Pr. The addition of Sm shows a significant effect on ZRE1 grain size in Figure 5, where the addition of 0.5 wt.% Sm reduces the grain size significantly by about 13% due to an increase in the coherency time of the alloy (Ahmad et al, 2017b).…”
Section: Figure 3 Xrd Pattern Of Zre1-xsm Alloysmentioning
confidence: 79%
“…The peak at the band 3000-3500 cm -1 indicates the OH stretching vibrations in all samples (Kusrini et al, 2021). In the sludge sample, the OH wave number was at 3744.40 cm -1 with a fairly wide peak.…”
Section: Ftir and X-ray Analysismentioning
confidence: 89%
“…Chitosan is an exemplary capping agent for the preparation of NPs in aqueous media. Chitosan is a versatile polysaccharide produced from the partial deacetylation of chitin that yields a biodegradable, biocompatible, and non-toxic biopolymer that has wide utility in advanced biomedical and therapeutic applications [19][20][21][22][23]. Chitosan displays antimicrobial properties, which relate to its glucosamine units and protolytic behavior that favors adhesion to bacterial surfaces with negative surface charges [24].…”
Section: Introductionmentioning
confidence: 99%